Cultural hegemony in the selected one-act plays of Valente Cristobal - Roldan, Sefania Gabrielle (2014.)
The zarzuela was an all-time favourite of both the elite and the masses since it staged performances with themes ranging from the grand to the ordinary. Because of its growing popularity, it was then adapted by the native Ilonggos as sarswela. This paper argues that the beliefs, values, and norms presented in the selected sarswelas, i.e. the one-act plays of Valente Cristobal, namely ?Ang Mga Viciohan? (1903); ?Madaya? (1904); ?Si Platon? (1907); ?Maimon nga Amay? (1908); and ?Asawa Balaye? (1910), mark the cultural hegemony in the period of sarswela?s prominence of Iloilo City. The researcher used Antonio Gramsci?s theory of cultural hegemony, which pertains to the attempt at homogenizing the culture of the bourgeois society and the working class, which was a means of the ruling class to maintain their power
Thesis (Undergraduate, Bachelor of Arts in Literature) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Valente Cristobal; Hegenomy; Plays